Italy - Bonetto, Cristian; Blasi, Abigail; Christiani, kerry; #aClark, Gregor; Dixon, Belinda; Garwood, Duncan; hardy, Paula; Sainsbury, Brendan; Wheeler, Donna; Williams, Nicola (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2016)
Recommends restaurants, accommodations, attractions, shopping, and entertainment; and provides information on transportation and planning itineraries.
At head of title: Lonely Planet.
"Rome pull-out map top sights in full detail, local secrets"--Cover.
Includes bibliographical references and index.
Keywords: Italy -- Guidebooks